Effect Of Ease Of Use Of Application, E-Service Quality And Benefit Perception Of E-Wallet Application On Customer Satisfaction - Liana, Eva; Fadli, Jul Aidil (Jurnal Ilmiah Manajemen Kesatuan, 2023)
Current developments have brought many significant changes in human life, one of which is in making payments when transactions are made by people who have started to switch to non-cash. Evidenced by the existence of an electronic transaction system called fintech. Financial Technology (fintech) was created by the world of the financial services industry with technology to operate financial mechanisms more easily through smartphones using electronic wallets (E-Wallet). This study aims to determine the effect of application ease of use, e-service quality and perceived benefits on customer satisfaction. This research was conducted on e-wallet application users aged 17 to > 35 years. The sampling method used purposive sampling with a total sample of 105 respondents. The number of statements given to respondents was 21 statement items. The data analysis technique used in this research is descriptive analysis, validity test, reliability test, classical assumption test and multiple linear regression analysis. The results of the research based on the analysis that has been carried out are that the ease of use of the application has a negative and insignificant effect on customer satisfaction, e-service quality has a positive and significant effect on customer satisfaction, and perceived benefits have a positive and significant effect on customer satisfaction. Keywords:Ease of Use of Applications, E-Service Quality, Perceived Benefits, Customer Satisfaction